Is there an influence of relative age on participation in non-physical sports activities? The example of shooting sports - Delorme, N.; Raspaud, M. (Journal of Sports Sciences, 2009)
The aims of this study were to test for the presence of a relative age effect among male (n = 119,715) and female (n = 12,823) members of the shooting sports federation, and to determine whether any such effect has an impact on dropout from the sport. For the boys and girls, the results show a uniform distribution of dropout. A relative age effect was not found for the girls, showing that in female shooting sports there is no such effect. For the males, a significant statistical relative age effect was not detected in the 18-20 and 13-14 year categories. However, a relative age effect was found among adults and the 11-12 and under 11 year categories. A significant "inverse" relative age effect was found for the 15-17 year group. Further qualitative research is needed to clarify which factors contribute to this asymmetric distribution of birth dates in French male shooting sports.